Effect of Presuperovulatory Treatment of Buserelin on Superovulatory Response and Embryo Recovery in Cattle under Subtropical Conditions of Meghalaya - KUMAR, S.; BARMAN, C.; DOLEY, S.; KADIRVEL, G.; BHARTI, P.K.; SINGH, V. (Indian Journal of Hill Farming, 2015)
An experiment was conducted with 24 healthy cyclic cows between 2nd to 5th lactation by under intensive system of rearing. The animals were randomly divided into Control (C) and Experiment (E) groups with 12 animals in each The control and experiment groups were again further subdivided in groups C1 and C2 & E1 and E2 comprising six in each. Onset of oestrus was considered as day 0 for superovulatory treatment. The animals of groups C1 and C2 & E1 and E2 were injected with 5 ml NSS (i/ml) & 21Î¼g GnRH (i/m) (Buserelin acetate) on day 8 of the oestrous cycle, respectively. Each of the experimental animals of groups C1and E1 was superovulated with 400 mg FSH (i/m) in divided and equal doses at 12 h intervals for four days on day 10 to 13 of the oestrous cycle and consequently, each of the experimental animals of groups C2 and E2 was also superovulated with 2000 I.U.PMSG injection (i/m) as single dose on day 10 of the oestrous cycle. PGF2Î± 2ml was injected (i/m) at morning time on day 12 of oestrous cycle. At the superovulatory oestrus, all the animals were bred three times at 12 h intervals using frozen semen. The animals were examined per rectally on day 6 of the induced oestrus after first insemination to detect the superovulatory response. Flushing was performed on day 7 of induced oestrus to retrieve embryos from the superovulated cows. In the present experiment, superovulatory response in GnRH treated groups of cows (groups E1 and E2) were found to be better as compared to that of the animals of control groups but the duration of induced oestrus (h) recorded in groups C2 (49.02 Â± 0.07 h) and E2 (50.40 Â± 0.27 h) were found to be significantly higher (P<0.05) than the value recorded in groups C1 and E1.